Architectural Design Of Information Systems Decision Support Of Lecturer Performance Assessment With Promethee Method (Case Study: Stmik Dci) - Andri Sukmaindrayana (Jurnal Mantik, 2022)
Lecturer performance evaluation activities are a college routine in improving internal quality on an ongoing basis. STMIK DCI Tasikmalaya currently does not routinely evaluate the performance of lecturers, implementing the university's tri dharma activities and other tasks. This study aims to design an information system architecture that supports a performance appraisal decision based on the criteria and sub-criteria of the assessment as a performance appraisal variable using the Prometheus method, where each criterion and sub-criteria, the assessment factors and alternatives, in this case, the lecturers are compared with one another to provide an output value of net flow and ranking that provides an assessment of each Lecturer's performance. This decision support information system helps in processing lecturer data, processing data on assessment criteria and sub-criteria, and processing assessments and processes using the Prometheus method. This is useful to facilitate decision-makers in assessing the Lecturer's performance so that the achievement value of the Lecturer's performance will be obtained. By using an object-oriented system design method, namely RUP (Rational Unified Process), which is iterative, and UML (Unified Modeling Language), which is used as a tool, The results of this study are in the form of a decision support information system architecture model and the implementation of its application using the MySQL database type and the Delphi programming language.